Impact of industrialization, urbanization, and financial development on energy consumption: Empirical evidence from India. Issue 3 (13th February 2020) - Sahoo, Malayaranjan; Sethi, Narayan
Abstract: This article examines the relationship between energy consumption, industrialization, urbanization, economic growth, and financial development in India from 1980 to 2017. The ARDL bound testing; Johansen & Juselius cointegration approach and Gregory & Hansen structural break cointegration technique confirm the long‐run relationship exists among variables. The result of long‐run analysis indicates that the industrialization, urbanization and economic growth play a vital role in increasing energy consumption in India. However, financial development indicates negative relation to energy consumption. The coefficient of error correction term is negative and statistically significant at 1% confidence level, it means last‐period's deviation from a long‐run equilibrium. It is clear from the results of Toda‐Yamamoto Causality, there is a unidirectional causality running from industrialization to energy consumption. However, there is bidirectional causality showing between energy consumption and urbanization, economic growth and energy consumption, and urbanization and Economic growth. Urbanization facilitates fuel switching, as decentralized rural energy sources like traditional wood‐burning are replaced by centralized energy sources. From the above findings, we argue that proper awareness should be made at the urban center regarding use of energy saving equipments and public infrastructure should be improved to harness the effect of urban agglomeration. As rapid development of energy intensive‐industries and economic activity in Indian economy, there is need of energy efficient technology in industry in order to reduce energy consumption.